2011
DOI: 10.1371/journal.pone.0020444
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-2 Expression Promotes TGF-β1-Mediated Epithelial to Mesenchymal Transition in Colorectal Cancer Cells

Abstract: Neuropilins, initially characterized as neuronal receptors, act as co-receptors for cancer related growth factors and were recently involved in several signaling pathways leading to cytoskeletal organization, angiogenesis and cancer progression. Then, we sought to investigate the ability of neuropilin-2 to orchestrate epithelial-mesenchymal transition in colorectal cancer cells. Using specific siRNA to target neuropilin-2 expression, or gene transfer, we first observed that neuropilin-2 expression endows HT29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 46 publications
7
96
1
1
Order By: Relevance
“…Other authors have reported similar findings in studies of Nrp1 [35] and Nrp2 [36]. In view of these findings, we hypothesize that Nrp1 plays a key role on the membrane of cells by capturing active or latent TGF-β1, activating the latent form, and enhancing TGF-β-receptor signaling.…”
Section: Role Of Nrps In Cancersupporting
confidence: 87%
“…Other authors have reported similar findings in studies of Nrp1 [35] and Nrp2 [36]. In view of these findings, we hypothesize that Nrp1 plays a key role on the membrane of cells by capturing active or latent TGF-β1, activating the latent form, and enhancing TGF-β-receptor signaling.…”
Section: Role Of Nrps In Cancersupporting
confidence: 87%
“…Although we have assessed downstream targets of the VEGF pathway and seen no changes, additional downstream effectors may still be contributing to melanoma cell proliferation. Recent studies have identified NRP2 expression as affecting the β-catenin and transforming growth factor-β1 pathways in human gastrointestinal and colorectal cancers, respectively [32,33]. As β-catenin and transforming growth factor-β1 have been implicated in melanoma tumorigenesis [34,35], these pathways may also be relevant to our current observations.…”
Section: Discussionsupporting
confidence: 57%
“…These expression data were substantiated by our finding that VEGF/NRP2 signaling regulates the expression of Bmi-1, a Polycomb group transcriptional repressor implicated in prostate tumorigenesis (16). Although a previous study had foreshadowed a role for NRP2 in the xenograft growth of colorectal carcinoma cells (37), our study is the first to demonstrate that an oncogenic pathway, i.e., c-Jun activation induced by PTEN loss, regulates NRP2. Moreover, our finding that NRP2 expression increases with Gleason grade is consistent with our previous finding that VEGF expression in cancer cells also increases with Gleason grade (20), supporting the hypothesis that autocrine VEGF/NRP2 signaling is characteristic of high-grade, aggressive prostate cancer.…”
Section: Discussionmentioning
confidence: 56%